Peculiarities of chicks kittiwakes Rissa tridactyla (Linnaeus, 1758) metabolism at cestodosis - M. M. Kuklina; V. V. Kuklin (Российский паразитологический журнал, 2016)
The results of the research of the parameters of the proteins, carbohydrates, lipids and minerals metabolisms of chicks kittiwakes (Rissa tridactyla) are presented. The comparative analysis of the biochemical parameters of blood plasma noninfected birds and birds infected by Alcataenia larina, Tetrabothrius immerinus and Diphyllobothrium dendriticum are carried out. The most remarkable changes in metabolism note for chicks infected by A. larina and D. dendriticum. The peculiarities of the impact of species of the cestodes on metabolism of chicks are discussed.